2007
DOI: 10.1007/s10298-007-0227-5
|View full text |Cite
|
Sign up to set email alerts
|

Les algues ont-elles une place en nutrition ?

Abstract: Ré sumé : La quantité de macro-algues transformées annuellement dans le monde est de plus de 9 millions de tonnes (poids frais). Premier débouché mondial en valeur et volume, les applications alimentaires directes (algue légume) concernent 75 % de cette production. L'algue est un aliment traditionnel qui présente un intérêt nutritionnel connu et exploité depuis de nombreuses années par les populations du Sud-Est asiatique. La valeur nutritionnelle des algues peut s'expliquer en grande partie par la présence co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
6
1
1
Order By: Relevance
“…Our results showed that our organism has no important amount of tannins. Hence, these results were in contrast with the previously reported literature, which revealed the presence of promising tannin content in the genus Arthrospira [6].…”
Section: Determination Of Tannins Qualitative Analysis Ofcontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results showed that our organism has no important amount of tannins. Hence, these results were in contrast with the previously reported literature, which revealed the presence of promising tannin content in the genus Arthrospira [6].…”
Section: Determination Of Tannins Qualitative Analysis Ofcontrasting
confidence: 99%
“…e nutritional value of spirulina can be due to its chemical composition, which is constituted of fibers, minerals, and proteins in large part, not that only but also the presence of secondary metabolites (vitamins, tannins), which are known to possess antioxidant and antibacterial effects. e chemical composition of spirulina exhibits other important benefits such as cosmetic, pharmacological, and therapeutic values [6].…”
Section: Comparison Of a Platensis Indigenous To The Moroccan Atlantic Coast At Laayoune With The Same Species From Different Collection mentioning
confidence: 99%
See 1 more Smart Citation
“…as 'aonori' in Japan; Ohno 1993), and since 1990 have been authorised for human food in France (Marfaing and Lerat 2007). Ulva species have also been grown in many parts of the world in pilot commercial systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Algae can be used in normally food use and special regimes with a unique place in the nutrition compared to other vegetables and other sources of nutrients (Denis et al, 2010;Marfaing & Lerat, 2007). Phycobiliproteins have antioxidant properties (Holdt & Kraan, 2011) and could be used in the prevention or treatment of degenerative diseases: cardiovascular, certain cancers, and eye linked to oxidative stress.…”
Section: Levels Found In Dry Algaementioning
confidence: 99%